RELATIVE STUDY OF FOOD HABITS ON A GROUP OF ATHLETIC AND NON-ATHLETIC STUDENTS - ALBU A.; ONOSE I.; NEGREA M.; HODORCĂ R.M; CRĂCANĂ I.1 (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
Nourishment is an external factor with an important role in maintaining children and teenagers' health and especially those who work out a lot and for a long time. The purpose of the study is to get to know the food habits of athletic students and compare them with those of the non-athletic ones. Hypothesis: athletic students' food habits should be different from those of the non-athletic ones, because the body nutritional need is different. Material and methods: the study was done on a group of 183 teenagers of ages between 14 and 17. Out of these, 94 study at Sports Highschool, Iasi and 89 at G. Ibraileanu, Iasi. The students filled in a questionnaire of weekly frequency of food consumption. The results were analysed using the Pearson Chi - Scuare test. Results: the daily morning intake is admitted by 42.62% students, the calculated differences on school group being statistically insignificant (χ²=2.156,Gl=3,p>0.05). Eggs are present in the children's menus especially 2-3 times a week (43.72%), the calculated differences being statistically insignificant (χ²=3.683,Gl=4,p>0.05). Vegetables are present in children's menus 4-6 times a week (30.60%) or daily (31.15%). The calculated differences are statistically insignificant (χ²=1.156,Gl=4,p>0.05) and guide us towards similar food habits of students of the two studied groups. Pasta is eaten especially once (37.70%) or 2-3 times a week, the calculated differences being statistically insignificant, too (χ²=3.816,Gl=4,p>0.05).Conclusions: the students of the group study show similar food habits, which is a problem because atheletic students have raised nutritional needs.